Analisis kemampuan pemecahan masalah matematis siswa dalam menyelesaikan soal volume tabung berdasarkan langkah-langkah polya - Alvian Tommy Winata; Tunggul Firman Bima Pamungkas; Wahyu Nur Hidayat; Sri Hartini; Nazwadera Marsya Noorrochma; Rissa Prima Kurniawati (Universitas PGRI Madiun, 2026)
This study aims to analyze the mathematical problem-solving skills of elementary school students regarding the volume of three-dimensional shapes based on Polya’s steps. The study employed a qualitative descriptive approach with five fifth-grade students from SDN 1 Mojo selected based on their problem-solving ability test results. Data were collected through written tests and documentation, then analyzed using the Miles and Huberman model. The results showed that students’ abilities varied at each stage of Polya’s model. Some students were able to understand the problem and formulate a plan accurately but still made errors during the execution stage, particularly in calculations and in understanding the concepts of diameter and radius. In addition, most students did not thoroughly check their answers, making the checking stage the least mastered. Therefore, students’ mathematical problem-solving skills need to be improved, particularly in the execution and checking stages.